Pengembangan Alat Permainan Edukatif Busy Book dalam Meningkatkan Aspek Perkembangan Anak - Suyadi, Suyadi; Zuniarsih, Zuniarsih (Pusat Studi Pendidikan Kreatifitas Anak Wadas Kelir Purwokerto, 2020)
Technological advances today require parents and teachers to be more creative and innovative in learning with children, in this case for early childhood. One of them can be attempted by learning media or playing children. Many varieties of learning tools or media can be used by teachers to help the development of children, one of which is busy book. The Busy book in this study was named